Vermicomposting for climate change mitigation and sustainable soil health: Organic waste management, nitrogen use efficiency, and ecosystem services - Rajan Bhatt; Vishnu D. Rajput; Mandapelli Sharath Chandra; Debjyoti Majumder; Ashok K. Garg; Govindaraj Kamalam Dinesh; Amarinder Singh Riar; Kunal Bhatt; Krishan K Verma; Mauro Wagner de Oliveira; Vicky Anand; Olga Biryukova (Universitas Sebelas Maret, 2025)
Environmental and agricultural systems are under constant threat from the ever-increasing amounts of eco-agricultural waste, which is the primary focus of this review. By utilizing scientific and environmentally friendly techniques to reuse and recycle organic waste, proper management can help reduce waste. This analysis assessed the potential of earthworm species in agriculture and the role of vermicompost in the long-term recycling of crop nutrients, specifically nitrogen (N) recovery, which is at 76%. Sustainable organic farming relies on a scientific understanding of organic material management and nitrogen use efficiency through the application of vermicompost. The emphasis is on reusing and recovering nutrients from vermicompost at carbon-to-nitrogen ratios of 10 - 23, which reduces emissions of reactive nitrogen gases, achieves soil fertility, and allows the application of fertilizers made from sustainable sources. Vermicompost improves the soil’s properties and mitigates the adverse effects of global warming. Based on literature reviews and numerous trials, a proposal has been put forth to emphasize the importance of vermicomposting technology in agroecosystems. Reducing pollution, improving waste management, and lowering health hazards are all significant issues that could play an important role. In conclusion, vermicompost is a win-win technology for sustaining today’s agricultural system. It enhances soil properties, increases land productivity, and reduces greenhouse gas emissions by decreasing chemical fertilizers.